Do Motion Controllers Make Action Video Games Less Sedentary? A Randomized Experiment - Elizabeth J. Lyons; Deborah F. Tate; Dianne S. Ward; Kurt M. Ribisl; J. Michael Bowling; Sriram Kalyanaraman (Journal of Obesity)
Sports- and fitness-themed video games using motion controllers have been found to produce physical activity. It is possible that motion controllers may also enhance energy expenditure when applied to more sedentary games such as action games. Young adults (N = 100) were randomized to play three games using either motion-based or traditional controllers. No main effect was found for controller or game pair (P > .12). An interaction was found such that in one pair, motion control (mean [SD] 0.96 [0.20] kcal ⋅ kg-1 ⋅ hr-1) produced 0.10 kcal ⋅ kg-1 ⋅ hr-1 (95% confidence interval 0.03 to 0.17) greater energy expenditure than traditional control (0.86 [0.17] kcal ⋅ kg-1 ⋅ hr-1, P = .048). All games were sedentary. As currently implemented, motion control is unlikely to produce moderate intensity physical activity in action games. However, some games produce small but significant increases in energy expenditure, which may benefit health by decreasing sedentary behavior.